Development of a Discovery Learning–Based Physics E-Book to Enhance Students’ Conceptual Understanding of Sound Waves - Gida Elisa; Heru Kuswanto; Aris Kurniawan; Nur Inayah Syar (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2026)
The rapid advancement of technology has profoundly influenced the field of education, particularly by enabling learning experiences that are more interactive and conceptually deep. The incorporation of mobile-based learning has emerged as a relevant approach to increase student involvement in mastering complex physics topics, such as sound waves. Accordingly, this study aims to design and evaluate a discovery learning–based physics e-book as an innovative instructional medium for senior high school students. The research adopts the 4D research and development framework—Define, Design, Develop, and Disseminate—and involves subject matter experts, media experts, and senior high school students as participants. The sampling technique used purposive sampling for experts and random sampling for students. Data collection was conducted through questionnaires and concept understanding tests, which were analyzed using descriptive statistics with reference to media feasibility criteria tables and N-Gain criteria. The results indicate that the developed e-book achieved an excellent validity level according to media and content experts and received positive feedback from users, making it highly feasible as a learning medium for physics on the topic of sound waves. An N-Gain score of 0.57 indicates a moderate increase in students’ conceptual understanding, showing that the discovery learning–based physics e-book serves as an engaging alternative for enhancing learning experiences. By combining academically relevant content with local cultural values, the e-book helps students relate physics concepts to their cultural context. These findings emphasize the need for innovative and contextual learning media to improve students’ understanding of physics, preserve local wisdom, and enhance the quality of physics education in Indonesia.